Implementation of Artificial Intelligence in Compiling School Digital Profiles to Improve Educational Branding: A Case Study of Muhammadiyah 1 Wuryantoro Junior High School - Hanifah Tria Intan Jelita; Rochman Hadi Mustofa (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The rapid advancement of digital technology over the past decade has fundamentally transformed educational ecosystems worldwide. Innovations such as artificial intelligence (AI), adaptive learning, learning analytics, and digital administration systems have reshaped how schools communicate, manage data, and build their institutional identity. In this context, digital transformation is no longer merely an instructional enhancement but has become a strategic necessity for educational institutions to maintain relevance and competitiveness in the digital era (Wang, 2024). Along with these developments, public expectations toward transparency, professionalism, and digital credibility of schools have also increased. Parents and prospective students increasingly rely on digital information such as websites, social media, and multimedia profiles when evaluating the quality of a school. Therefore, the construction of a strong digital profile plays a crucial role in educational branding, influencing public perception and shaping institutional identity (Keller & Swaminathan, 2020; Wibowo & Lestari, 2021). A well-developed school digital profile not only presents factual information but also functions as a strategic communication tool that showcases values, programs, achievements, and cultural identity. However, many schools especially those with limited human resources struggle to produce professional and competitive digital publications. Challenges typically arise from limited design skills, inadequate documentation equipment, and low digital literacy among teachers. As noted by Li & Chen (2023), AI offers transformative potential to address these limitations by supporting automated content generation, enhancing visual materials, and accelerating digital production processes. In educational contexts, AI provides an accessible and efficient solution for schools seeking to strengthen their branding without requiring advanced technical expertise. SMP Muhammadiyah 1 Wuryantoro represents a relevant case study because it has recently begun integrating AI to develop its digital school profile and improve institutional branding. While previous documentation was fragmented, inconsistent, and limited in visual quality, the adoption of AI tools such as AI-based text generation, photo enhancement applications, and automated graphic design platforms has enabled the school to redesign its digital presence more systematically and professionally. Despite the relevance of this topic, existing research on AI implementation in school branding remains limited, with most studies still focusing on classroom learning and administrative automation. Thus, there is a gap in understanding how AI contributes specifically to digital profile development as a branding strategy particularly in schools with limited human resources. Based on this gap, the present study aims to analyze the implementation of AI in developing the digital school profile of SMP Muhammadiyah 1 Wuryantoro and to evaluate its impact on content quality, school branding, and teacher digital literacy. This study positions AI not only as a technical tool but also as an enabler for institutional transformation and capacity building.